2009
DOI: 10.3310/hta13410
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of bariatric (weight loss) surgery for obesity: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
570
2
25

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 857 publications
(626 citation statements)
references
References 130 publications
14
570
2
25
Order By: Relevance
“…Bariatric surgery has emerged as the first (and, so far, only) technology associated with significant success against severe obesity [29][30][31] and its associated comorbidities [32] for a large proportion of treated patients. The procedure has demonstrated significant cost savings and return on investment for patients with class 3 obesity (i.e., BMI C40.0 patients) [33][34][35][36][37][38][39][40][41] and may be of benefit for other categories of patients [19].…”
Section: Three Recent Trends Suggest That Obesity and Its Challenges mentioning
confidence: 99%
“…Bariatric surgery has emerged as the first (and, so far, only) technology associated with significant success against severe obesity [29][30][31] and its associated comorbidities [32] for a large proportion of treated patients. The procedure has demonstrated significant cost savings and return on investment for patients with class 3 obesity (i.e., BMI C40.0 patients) [33][34][35][36][37][38][39][40][41] and may be of benefit for other categories of patients [19].…”
Section: Three Recent Trends Suggest That Obesity and Its Challenges mentioning
confidence: 99%
“…An economic evaluation by Picot et al supported the cost-effectiveness of bariatric surgeryinduced weight loss [11]. However, health technology assessments specify that bariatric surgery is cost-effective in patients with diabetes (EOSS stage 2).…”
Section: The Role Of Edmonton Obesity Staging System In Bariatric Surmentioning
confidence: 99%
“…Recently, a systematic review concluded that bariatric surgery appears to be a clinically and cost-effective intervention for moderate-to-severely obese people compared with non-surgical interventions [44]. However, uncertainties persist and further research is required.…”
Section: Clinical Benefitsmentioning
confidence: 99%